Behind the Kitchen Doors: Unveiling Post-COVID Challenges and Sustainable Solutions for Chefs in the Hospitality Sector - Ozbasar, Kurtulus; Saydam, Mehmet Bahri; Ozturen, Ali; Ardahan, Mehmet Guven (Mdpi, 2024)
This study aims to provide a comprehensive exploration of the multifaceted barriers experienced by chefs working within the dynamic and demanding landscape of the hospitality industry. By delving into the intricacies of their work environment, we aim to shed light on the day-to-day hurdles they encounter, offering a detailed understanding of the obstacles they face. In our study, we employed a qualitative research framework to investigate the challenges faced by chefs in the hospitality sector, focusing on their unique experiences. Our data collection involved in-depth interviews with chefs in North Cyprus. Our findings reveal seven predominant problems within the culinary industry, encompassing workload and stress, customer expectations, menu creativity and innovation, team dynamics, career advancements, ingredient sourcing, and technology and automation. These insights serve as a valuable resource for industry professionals and researchers alike who are committed to enhancing the culinary profession and elevating the dining experience for customers. The originality of this study lies in its unique focus on addressing the underrepresented area of research concerning the specific barriers faced by chefs in the tourism and hospitality industry. By exploring the day-to-day hurdles encountered by chefs, this research contributes to both academic knowledge and practical insights that can enhance industry practices and ultimately improve the quality of dining experiences for guests.
Keywords: chefs; hospitality; restaurant; post-COVID challenges; sustainable decent work; Leximancer